2015
DOI: 10.1371/journal.pone.0134156
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin Attenuates Iron Accumulation and Oxidative Stress in the Liver and Spleen of Chronic Iron-Overloaded Rats

Abstract: ObjectivesIron overload is now recognized as a health problem in industrialized countries, as excessive iron is highly toxic for liver and spleen. The potential use of curcumin as an iron chelator has not been clearly identified experimentally in iron overload condition. Here, we evaluate the efficacy of curcumin to alleviate iron overload-induced hepatic and splenic abnormalities and to gain insight into the underlying mechanisms.Design and MethodsThree groups of male adult rats were treated as follows: contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
84
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 46 publications
7
84
0
1
Order By: Relevance
“…Curcumin reduced oxidative stress in thalassaemia patients and decreased iron overload and oxidative stress in the liver and spleen of chronic iron-overloaded rats. 7,16 Thus, curcumin may influence the sickle microenvironment that includes large quantities of cell-free iron due to hemolysis and oxidative stress. Treatment with curcumin and/or CoQ10 could be a promising alternative strategy to reduce pain in SCA.…”
mentioning
confidence: 99%
“…Curcumin reduced oxidative stress in thalassaemia patients and decreased iron overload and oxidative stress in the liver and spleen of chronic iron-overloaded rats. 7,16 Thus, curcumin may influence the sickle microenvironment that includes large quantities of cell-free iron due to hemolysis and oxidative stress. Treatment with curcumin and/or CoQ10 could be a promising alternative strategy to reduce pain in SCA.…”
mentioning
confidence: 99%
“…In addition, increased lipid peroxidation during liver damage was reported (29,30,36). It has been demonstrated that imbalance between oxidant and antioxidant factors, occurred in the iron overload condition, which resulted in reduction of enzyme activity such as catalase (31,34). In the current study, iron overload resulted in various adverse effects, such as increase in ALT, AST, and ALP activity and MDA level, as well as decreased CAT activity, which indicates liver damage.…”
Section: Discussionmentioning
confidence: 51%
“…The role of iron in the development of hepatic injuries in several clinical and experimental conditions has commonly been studied by induction of an iron overload condition (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations